New species of Potamocoris Hungerford (Heteroptera, Potamocoridae) from Costa Rica and a key to the species - Herrera, Federico (2014)
A new potamocorid species, Potamocoris sitesi NEW SPECIES, with its two wing morphs (coleopteroid and macropterous) are described from Costa Rica. Descriptions are supported with photographs and illustrations. Parameres become progressively narrower, ending in a sharp needle-like point. This is the third species of Potamocoris known from Central America. A key to the species of the genus is provided.